Customer Loyalty Is Influenced By Brand Ambassadors And Co-Creation With Moderating Currency (Study On Ms. Glow Users In Bekasi Regency Area) - Surya Bintarti; Catia Laila Ferdiansyah (Dinasti Publisher, 2024)
Along with developments in this modern era, women are required to be able to take care of themselves. Ms Glow is one of the lines under the auspices of PT. Cosmetika Cantik Indonesia was founded in 2013. Based on existing data, the Ms Glow facial care product is in third place but has won the Indonesian Best Brand Award (IBBA) in 2020 in the facial care category which is sold exclusively. This Ms Glow product has various kinds of skincare products with thousands of resellers in various cities in Indonesia.This research aims to test how much influence brand ambassadorship, co-creation has on customer loyalty which is moderated by currency in Ms Glow beauty products. This research was conducted within the boundaries of Bekasi Regency, the method used was a quantitative method with a sample size of 108 people, the technique used in sampling was nonprobability sampling with a purposive sampling method.This research tests correlation and regression with the help of the SMSRTPLS 3.0 program which is used to test validity and reliability, goodness of fit models and hypotheses. This research shows the results that: 1). brand ambassadors have an insignificant positive effect on customer loyalty, 2). co-creation has a significant positive effect on customer loyalty, 3). brand ambassador which is moderated by currency has a positive but not significant effect, 4). co-creation moderated by currency has no effect on customer loyalty.